Ekspresi dan Aktivasi Reseptor Glukokortikoid serta Ekspresi Heat Shock Protein- 90 pada Sel Limfosit Penderita Sindrom Nefrotik Idiopatik - Khairiyadi, Khairiyadi; Subandiyah, Krisni; Fitri, Loeki Enggar (Jurnal Kedokteran Brawijaya, 2009)
Glucocorticoid receptors (GR) have an important role in the resistance of steroid therapy . Previous studies showed  significant  difference  activation  and  expression  of  GR  between  Steroid  Resistant  Nephrotic Syndrome (SRNS) and Steroid Sensitive Nephrotic Syndrome (SSNS), however the other studies showed contrastive result. Previous studies also revealed Hsp-90 had an important  role in  GR activation. The aim of this study was to determine the differences expression and activation of GR and also Hsp-90 expression in lymphocytes  cytoplasm  and  nucleus  between  SRNS  and  SSNS  patients.  A  Cross-sectional  study  was conducted  to  40  children  (20  SRNS  and  20  SSNS  patients).  Double  stainning  immunocytochemistry  of lymphocytes  was  performed.  The  GR  expression  and  activation  were  determined  by  counting  amount  of lymphocytes  that  express GR and Hsp-90 among 200 under light  microscope with 1000x magnification. The differences  of  activation  and  activation  of  GR  and  Hsp-90  in  cytoplasm  and  nucleus  were  analyzed  with independent t-test and the correlation was analyzed with Pearson correlation.